LEADER AND PEOPLE CONCEPTS EMBODIED IN METAPHORS FOUND IN PENYAMBUNG LIDAH RAKYAT INDONESIA: AN AUTOBIOGRAPHY BOOK OF SOEKARNO - Yanisha Dwi Astari; Armita Novriana Rambe (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The paper aims to investigate the kinds of metaphors found in the book Penyambung Lidah Rakyat Indonesia: An Autobiography of Soekarno, which is written based on the interview with Soekarno, the first president of Indonesia who pronounced proclamation of Indonesian independence. The identified metaphors are focused on the ones related to the concepts of leader and people. The categorizations are based on Lakoff and Johnson (2003) distinction of conceptual metaphor: structural, orientational, and ontological. The approach used in this study is qualitative. There are 28 data of metaphors related to the concepts of leader and people found in the autobiography book of Soekarno. Based on the analysis, it shows that the concepts of leader and people which are embodied in the metaphors are that leader is the backbone of a family; he/she is born from and raised by people, which inevitably belong to his people (as their property or what people belong to), and as the leader grows up, the offspring roles becomes more significant as the ear, mouth, and the extension of people’s tongue to the utmost. As much important as the leader is, people are also perceived as the nutrition and motor to make the leader alive and keep surviving.